IN VITRO ACTIVITY OF CEFTAZIDIME-AVIBACTAM AND COLISTIN AGAINST CARBAPENEM-RESISTANT PSEUDOMONAS AERUGINOSA CLINICAL ISOLATES - Tuğrul Hoşbul; Canset Nur Aydoğan; Sinem Kaya; Orhan Bedir; Hande Özcan; Ramazan Gümral (İstanbul Tıp Fakültesi Dergisi)
Objective: Infections caused by multi drug-resistant Gram-negative bacilli are increasingly reported worldwide. Ceftazidime-avibactam is a novel antibiotic combination that presents good activity against carbapenem-resistant Enterobacterales members and Pseudomonas aeruginosa isolates. The objective of this study was to evaluate the in vitro activity of ceftazidime-avibactam and colistin against carbapenem-resistant P. aeruginosa isolates. Materials and Methods: A total of 100 carbapenem-resistant and non-duplicate P. aeruginosa isolates obtained from patient samples in our hospital between 2016-2021 were included in the study. The isolates were identified by MALDI-TOF MS (Bruker Daltonics, Germany). The minimum inhibitory concentration (MIC) values of meropenem, colistin, ceftazidime, and ceftazidime-avibactam were determined by the broth microdilution method. The presence of carbapenemase genes bla KPC, bla NDM, bla OXA-48, bla IMP, and bla VIM were investigated using PCR. Results: Carbapenemase genes were not detected among the isolates except for one isolate producing bla VIM. The susceptibility rates of ceftazidime-avibactam and colistin were 90% (n=90) and 100% (n=100), respectively. The MIC50 and MIC90 values for meropenem, ceftazidime, ceftazidime-avibactam, and colistin against P. aeruginosa isolates were found to be 32/64, 8/64, 4/8, 0.5/2 µg/mL, respectively.Conclusion: The data suggests that ceftazidime-avibactam exhibits as a viable alternative for the treatment of carbapenem-resistant P. aeruginosa isolates. It’s noteworthy that colistin resistance was not detected among the study isolates. Rational use of antibiotics should be emphasized to prevent the development of antibiotic resistance. Surveillance of ceftazidime-avibactam and colistin should be followed up with routine antimicrobial susceptibility tests.